Impacts of proactive personality on students' academic achievement: a moderated mediation model - Liu, Dongmei; Lin, Ye; Jin, Yongchao; Li, Zongjin; Fu, Kexin; Yang, Rui (Frontiers in Psychology, 2025)
IntroductionA proactive personality, characterized by an individual's tendency to take initiative and actively shape their environment, has been increasingly recognized as a critical factor in academic success. Drawing on Job Demands-Resources (JD-R) theory and proactive motivation frameworks, this study investigates the relationship between proactive personality and academic achievement, focusing on the mediating role of academic self-efficacy and the moderating role of perceived social support.MethodData on proactive personality, academic self-efficacy, perceived social support, and academic achievement were gathered through WJX, yielding a total of 1,153 completed questionnaires. Statistical analyses were performed using SPSS and Mplus software, including correlation analysis, principal component analysis, t-tests, and parametric statistics.ResultsResults indicate that proactive personality positively predicts academic achievement, with academic self-efficacy serving as a significant mediator. Furthermore, perceived social support moderates this relationship, enhancing the positive effects of proactive personality on academic achievement through strengthened self-efficacy.DiscussionThe study highlight the importance of fostering proactive behaviors and providing robust social support systems in educational settings to promote students' academic success.